Medialogues - Chen, Evelyn; Siya, Chen; Seah, Lianne; Wong, Patrick (Singapore Ngee Ann Polytechnic, 2005)
SYMC 2005 was Singapore's inaugural conference providing a platform for the exchange of views and research about youth-related issues in mass media. It was organised by a team of final-year Mass Communication students from the School of Film & Media Studies (FMS), Ngee Ann Polytechnic. SYMC aims to encourage Singaporean youths to be active and engaged in issues that matter to them and to foster a conducive environment for youths to come together, network, and share ideas.

This book is a selection of 10 papers from the inaugural Singapore Youth & Media Conference (SYMC), organised by Ngee Ann Polytechnic's School of Film & Media Studies in January 2005.
Includes bibliographical references.
A gift of Dr. Victor T. Valbuena.
Keywords: Mass media and youth -- Singapore -- Congresses; Mass media -- Influence -- Congresses; Mass media and culture -- Singapore -- Congresses; Internet and teenagers -- Singapore -- Congresses